2018
DOI: 10.1093/esr/jcx089
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Material Deprivation for 25 EU Countries: Risk and Level Perspectives, and Distinctiveness of Zeros

Abstract: and the participants of OPHI Seminars for their valuable comments on the draft of the paper. I also would like to thank to the editors and four anonymous referees whose useful comments and suggestions, I believe, improved the paper significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The results obtained in this research prove that scoring zero on the material deprivation scale is a qualitatively different phenomenon to scoring at least one. Thus, using zero-inflated count models, Bedük (2018) shows that individuals with zero deprivation items have significantly distinct profiles to those who experience at least one deprivation item. Other relevant papers on the intensity of material deprivation are Bárcena-Martín et al (2014) and Busetta et al (2016).…”
Section: Materials Deprivation Research In the Eumentioning
confidence: 95%
See 4 more Smart Citations
“…The results obtained in this research prove that scoring zero on the material deprivation scale is a qualitatively different phenomenon to scoring at least one. Thus, using zero-inflated count models, Bedük (2018) shows that individuals with zero deprivation items have significantly distinct profiles to those who experience at least one deprivation item. Other relevant papers on the intensity of material deprivation are Bárcena-Martín et al (2014) and Busetta et al (2016).…”
Section: Materials Deprivation Research In the Eumentioning
confidence: 95%
“…Other socio-demographic factors such as gender, age, health status, and place of residence have also been examined by many authors. In particular, Bedük (2018) and Nelson (2012) found that women are generally more deprived than men. Moreover, Hicks (2016) and Bárcena-Martín et al (2014) revealed that living in a female-headed household significantly increases the risk of MD.…”
Section: Correlates Of Materials Deprivation In the Eumentioning
confidence: 99%
See 3 more Smart Citations